A contemporary review of radiation pneumonitis. Issue 4 (July 2020) - Ullah, Tofura; Patel, Harsh; Pena, Grace M.; Shah, Rakesh; Fein, Alan M.
Abstract : Purpose of review: The current article reviews recent literature and summarizes the current understanding, diagnosis, risk, predictors, and management of radiation pneumonitis. Recent findings: We discuss the different parameters that contribute to radiation toxicity, the potential biomarkers that predict the risk, and mitigators of radiation pneumonitis. Summary: Radiotherapy aims to provide care and a better quality of life in cancer patients however with complications. Radiation pneumonitis is important to recognize to appropriately plan and care for this population.